Effectiveness of Gelatin Extracted from Chicken Claws as A Natural Preservatives for Beef and Fish - Ganjar Fadilah; Pramudita Putri Kusuma; Teguh Endah Saraswati (UNIVERSITAS SEBELAS MARET (UNS), 2014)
Gelatin has been successfully extracted from chicken clawsby acid hydrolysis method through four major stages of degreasing, demineralization, extraction and drying. The yield of extracted gelatin obtained from wet chicken claws was about 6.21 % (w/w). The effectiveness of gelatin as preservative applied in beef and fish was physically, chemically and microbiologically studied by organoleptic analysis, peroxide test, bacteria inhibition test and number calculation, respectively. Organoleptic analysis by hedonic test shows there were significant differences for color and texture parameters between gelatin coated samples and control samples at concentrations of 1:1 (w/w). Peroxide number analysis by iodometry indicates the use of gelatin in the preservation of meat and fish decreased the oxidation number. The result of inhibition test againts Staphylococcus aureus bacteria shows the gelatin concentration of 20 % provided greatest halo zone diameter (inhibitory region) as 19.44 ± 2.11 mm. The colony bacteria test shows the use of gelatin potentially inhibited the growth of bacteria up to 75 %. Overall, the results conclude that gelatin extracted from chicken claws has the potential activities as a natural preservative for beef and fish.